Phycoerythrin from Colaconema sp. Has Immunostimulatory Effects on the Whiteleg Shrimp Litopenaeus vannamei and Increases Resistance to Vibrio parahaemolyticus and White Spot Syndrome Virus - Po-Tsang Lee; Jing Huang; Chin-Yi Huang; Zi-Xuan Liu; Han-Yang Yeh; Huai-Ting Huang; Li-Li Chen; Fan-Hua Nan; Meng-Chou Lee (Animals, 2021)
We investigated whether phycoerythrin (PE), a pigment sourced from marine algae, could act as an immunomodulatory agent in whiteleg shrimp (Litopenaeus vannamei). To this end, PE was extracted and purified from a PE-rich macroalgae, Colaconema sp. Our in vitro analysis demonstrated that PE enhanced prophenoloxidase and phagocytosis activity but inhibited the production of reactive oxygen species in hemocytes. Additionally, the PE signal could be detected using an in vivo imaging system after its injection into the ventral sinus of the cephalothorax of whiteleg shrimp. The expression profiles of fourteen immune-related genes were monitored in hemocytes from whiteleg shrimp injected with 0.30 μg of PE per gram of body weight, and crustin, lysozyme, penaiedin 4, and anti-lipopolysaccharide factor showed up-regulated post-stimulation. The induction of immune genes and enhancement of innate immune parameters by PE may explain the higher survival rates for shrimp that received different doses of PE prior to being challenged with Vibrio parahaemolyticus or white spot syndrome virus compared to controls. Combined, these results show that PE from Colaconema sp. can differentially stimulate the immune response of whiteleg shrimp in vitro and in vivo and could potentially be used as an immunomodulator in shrimp culture.